PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PADA PT. BANK RAKYAT INDONESIA Tbk - Damirah Damirah; Andi Tenri Uleng Akal; Sri Wahyuni Nur (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2023)
This study aims to determine the effect of Corporate Social Responsibility on Financial Performance at PT. Bank Rakyat Indonesia, Tbk which is listed on the Indonesia Stock Exchange. Financial performance in this study is measured using a financial ratio, namely the Return On Equity (ROE) ratio. This research is a quantitative research with descriptive method. The data source in this study is secondary data obtained from the company's financial statements from 2018 to 2022. The data collection technique is carried out using a documentation technique where the data obtained comes from the official website of the Indonesia Stock Exchange. The analytical method used in this research is simple linear regression analysis using SPSS 26 software. The hypothesis testing in this study uses the t-test and correlation coefficient test and coefficient of determination test (R2). The results showed that simple linear regression analysis showed that ROE = 3,384 - 0,019 + e, t- value is -0,095 and significance value of -0.930 > 0.05, it was concluded that Corporate Social Responsibility had a negative and not significant effect on the financial performance of PT. Bank Rakyat Indonesia, Tbk which is listed on the Indonesia Stock Exchange from 2018 to 2022 so the hypothesis is rejected. The correlation coefficient test results are 0.055, which means that the effect of Corporate Social Responsibility (CSR) on financial performance has a